E-government services implementation: is it a need? - Kamarudin, Syafila; Omar, Siti Zobidah; Bolong, Jusang; Osman, Mohd Nizam (Human Resource Management Academic Research Society, 2018)
The Malaysian government has initiated e-service to embrace the use of modern information communication technology (ICT) in delivering services to its citizen. One of its e-service provider pertaining to online government service is My E.G. Services Berhad; which was established in 2000. It is a private company which has been given a concession by the government to conduct an online government transactions services. This article discussed on the use of MyEG services that will be viewed from the development perspective that took place, especially in Malaysia. In addition, it also discussed on the concept of e-government and the implementation that has yet to be undertaken in order to ensure the MyEG services can be used optimally in the course of daily work.